Combined blockade of the histamine H1 and H4 receptor suppresses peanut‐induced intestinal anaphylaxis by regulating dendritic cell function. Issue 11 (3rd August 2016) - Wang, M.; Han, J.; Domenico, J.; Shin, Y. S.; Jia, Y.; Gelfand, E. W.
Abstract: Background: Signaling through histamine receptors on dendritic cells (DCs) may be involved in the effector phase of peanut‐induced intestinal anaphylaxis. Objectives: The objective of this study was to determine the role of histamine H1 (H1R) and H4 receptors (H4R) in intestinal allergic responses in a model of peanut allergy. Methods: Balb/c mice were sensitized and challenged with peanut. During the challenge phase, mice were treated orally with the H1R antagonist, loratadine, and/or the H4R antagonist, JNJ7777120. Bone marrow‐derived DCs (BMDCs) were adoptively transferred to nonsensitized WT mice. Symptoms, intestinal inflammation, and mesenteric lymph node and intestine mucosal DCs were assessed. Effects of the drugs on DC chemotaxis, calcium mobilization, and antigen‐presenting cell function were measured. Results: Treatment with loratadine or JNJ7777120 individually partially suppressed the development of diarrhea and intestinal inflammation and decreased the numbers of DCs in the mesenteric lymph nodes and lamina propria. Combined treatment with both drugs prevented the development of diarrhea and intestinal inflammation. In vitro, the combination suppressed DC antigen‐presenting cell function to T helper cells and DC calcium mobilization and chemotaxis to histamine. Conclusion: Blockade of both H1R and H4R in the challenge phase had additive effects in preventing the intestinal consequences of peanut sensitization and challenge. These effects were mediated through the limitation of mesenteric lymph node and intestinal DC accumulation and function. Identification of this histamine H1R/H4R‐DC‐CD4 + T‐cell axis provides new insights into the development of peanut‐induced intestinal allergic responses and for prevention and treatment of peanut allergy.